MODAL SOSIAL DAN KONTRIBUSI EKONOMI PEDAGANG SAYUR KELILING DI SEMARANG (Forum Ilmu Sosial, 2012)
Problems to be solved in this study are (1) what lies behind the men became itinerant greengrocer?, (2) how the itinerant greengrocer build a social network with distributors, fellow merchants and consumers?, (3) what social norms that became agreement of the itinerant greengrocer who ensure the continuity of their business? (4) what the contribution of itinerant greengrocer to the family economy, (5) how the quality of their lives?This study used a qualitative approach and case studies. This study took place in the  city  of  Semarang.  Street  Vendors  areas  studied  were  Gunungpati  District,  where  they  sell  vegetables  around.  The  samples  taken  in   a purposive and respondents taken as many as 6 people merchants. The data was taken with observation techniques, interviews, and focus group discussion. Things that can not be taken with the three techniques, conducted with the study of literature. To measure the validity of data used triangulation techniques. The results were analyzed with qualitative analysis techniques (reduction, presentation, and drawing conclusions). From the results of research and field findings, it can be concluded (1) itinerant greengrocer has characteristics different from any other street vendors, which is mostly done by men, in trading on a motorcycle, and working in residential areas of dense population, (2) they become itinerant greengrocer, because there are no other jobs are more promising, (3) social capital merchants, mainly low membership in the association and has no contribution to the economic development of households, while the social capital of social networks and trust they have thus contributing significantly to the continuity business, (4) quality of life of itinerant greengrocer is relatively low, since the daily income is only enough for family consumption needs. Just in terms of freedom of component as part darei quality of life, they have it because they do not depend in selling to anyone, except to the agent.Based on the results of research and field findings, it is suggested that (1) vegetable traders are generally not affordable by the government and financial institutions, hence the need to be nurtured and empowered them to have access in developing the capital, and (2) most traders are not members of associations, therefore need established or included in the association of merchants who provide security and comfort in its hold.